2014
DOI: 10.1111/jfbc.12063
|View full text |Cite
|
Sign up to set email alerts
|

In VitroCalcium-Chelating and Platelet Anti-Aggregation Activities of Soy Protein Hydrolysate Modified by the Alcalase-Catalyzed Plastein Reaction

Abstract: Soy protein hydrolysate (SPH) (1 mg/mL), generated by alcalase, had a calcium‐chelating activity of 41 mg/g peptide. The alcalase‐catalyzed plastein reaction of SPH was carried out in different media: ethanol–water, methanol–water and water. The effects of SPH and of resulting modified hydrolysates on calcium‐chelating activities and inhibition of calcium precipitation and platelet aggregation were assessed in vitro. The optimum ethanol concentration, alcalase level and reaction temperature for the plastein re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It has been reported that the Ca‐chelating capacity of WPH obtained at different hydrolysis periods ranged from 23.9 to 34.9 mg g −1 (Cai et al ., ). Zhang & Zhao () showed that soy protein hydrolysate generated by alcalase had a calcium‐chelating activity of 41 mg g −1 peptide. Hence, the SCOHs are suitable for producing peptide–calcium complexes.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the Ca‐chelating capacity of WPH obtained at different hydrolysis periods ranged from 23.9 to 34.9 mg g −1 (Cai et al ., ). Zhang & Zhao () showed that soy protein hydrolysate generated by alcalase had a calcium‐chelating activity of 41 mg g −1 peptide. Hence, the SCOHs are suitable for producing peptide–calcium complexes.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that, when Alcalase is used to hydrolyze soy protein, the hydrolysate is rich in calcium-chelating activity, but if the reaction conditions are optimized J o u r n a l P r e -p r o o f using different media (water, ethanol-water, methanol-water), the calcium-chelating activities could be improved [564]. In another paper, casein and soybean proteins were hydrolyzed with Alcalase and trypsin [565].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The antioxidative property of plastein was implicated in the cytoprotective activity of Phe- and Tyr-enriched plastein in H 2 O 2 - and galactosamine-induced damage to cultured rat hepatatocyte; the plastein increased cell viability and decreased malondialdehyde content and lactate dehydrogenase leakage associated with the hepatocyte damage [62] . Furthermore, plastein reaction was reported to improve the in vitro anticoagulation (inhibition of platelet aggregation) activity of soybean protein-derived plastein based on increased activated partial thromboplastin and prothrombin time [60] . These findings have added a new perspective to the application of plastein for the development of health-promoting products.…”
Section: Reemergence Of Plastein For Potential Nutraceutical Applicatmentioning
confidence: 99%